1998
DOI: 10.1182/blood.v91.10.3734
|View full text |Cite
|
Sign up to set email alerts
|

Lyn Physically Associates With the Erythropoietin Receptor and May Play a Role in Activation of the Stat5 Pathway

Abstract: Protein tyrosine phosphorylation plays a crucial role in signaling from the receptor for erythropoietin (Epo), although the Epo receptor (EpoR) lacks the tyrosine kinase domain. We have previously shown that the Jak2 tyrosine kinase couples with the EpoR to transduce a growth signal. In the present study, we demonstrate that Lyn, a Src family tyrosine kinase, physically associates with the EpoR in Epo-dependent hematopoietic cell lines, 32D/EpoR-Wt and F36E. Coexpression experiments in COS7 cells further showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…These results were also compatible with the results of RQ‐PCR, and suggest that the mechanism of imatinib‐resistance in MYL‐R may be different from that of K562‐R and LAMA‐R (13), and that the Lyn‐associated resistance mechanism may be diverse among cell types. The expression of STAT5, considered one of the downstream target molecules of BCR‐ABL (29) and of Lyn (30, 31), was slightly elevated in MYL‐R when compared with MYL. Furthermore, phosphorylated STAT5 in MYL‐R was markedly elevated when compared with MYL or K562 cells, indicating that high expression of active Lyn in MYL‐R may have resulted in phosphorylation of its substrate, STAT5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were also compatible with the results of RQ‐PCR, and suggest that the mechanism of imatinib‐resistance in MYL‐R may be different from that of K562‐R and LAMA‐R (13), and that the Lyn‐associated resistance mechanism may be diverse among cell types. The expression of STAT5, considered one of the downstream target molecules of BCR‐ABL (29) and of Lyn (30, 31), was slightly elevated in MYL‐R when compared with MYL. Furthermore, phosphorylated STAT5 in MYL‐R was markedly elevated when compared with MYL or K562 cells, indicating that high expression of active Lyn in MYL‐R may have resulted in phosphorylation of its substrate, STAT5.…”
Section: Resultsmentioning
confidence: 99%
“…Lyn plays a important role in the activation of signaling pathways such as JAK2/STAT5, PI3K, and MAP kinase (30, 40). On the other hand, active Lyn kinase may partially block ERK activation or accelerate ERK inactivation (41).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the biased signalling was not a consequence of altered JAK2 catalytic mechanisms, but rather a result of utilizing an alternate tyrosine kinase. This may well be the case for other class I receptors which have been shown to associate with SFKs such as the prolactin receptor [ 106 , 107 ], EPO receptor [ 108 , 109 ], IL-6 receptor [ 110 ], GM-SCF receptor [ 111 113 ], the TPO receptor and others [ 114 ].…”
Section: Signalling Biasmentioning
confidence: 99%
“…In contrast to EPOR, TPOR is a much more potent activator of the MAPK pathway and STAT3 signaling [ 53 ]. Conversely, it has been shown that EPOR interacts with LYN kinase, which can bind to JAK2 and affects STAT5 [ 54 ]. EPOR and TPOR signaling is limited by a negative feedback loop employing SHP1 and SHIP phosphatases and suppressors of cytokine signaling (SOCS1, SOCS3) [ 49 , 55 , 56 ].…”
Section: Ontogeny Of Thrombocytes and Erythrocytesmentioning
confidence: 99%